(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the breakdown of COVID-19 pandemic also known as Serious Acute Respiratory Syndrome Corona virus-2 is an infectious disease that is released from an infected sick person. This spreads quickly through close contact with anyone infected. Institutions suffer a great deal from practically closed globally if the current situation is not going to change. Deep Learning has proven its effectiveness in recognition and classification through image processing. The research study uses deep learning techniques in distinguishing facial recognition and recognize if the person is having issues in the body temperature , respiration and pulse rate or not. The dataset collected and achieved an accuracy rate of 96% as to the performance of the trained model. The system develops a Raspberry Pi-based real-time face- patient monitoring and recognition that alarms and captures the facial image if the person detected and send the location to the nearly hospital. This study is beneficial in combating the spread of the virus and avoiding contact with the virus.